Odpowiedzi

2009-12-01T15:47:53+01:00
X - pierwsza liczba
y - druga liczba

otrzymujemy układ równań

x/y=3/2
x-6=3(y-6)

x=(3/2)y
(3/2) y-6=3y-18

x=(3/2)y
(3/2)y-3y=-18+6

x=(3/2)y
(-3/2)y=-12 mnozymy przez (-2/3)

x=(3/2)y
y=-12 razy(-2/3)

x=(3/2)y
y=8

x=(3/2)8
y=8

x=12
y=8
8 3 8
2009-12-01T15:53:57+01:00
X/y=3/2
x-6=3(y-6)

2x=3y /:3
x-6=3y-18

y= 2/3x
x-6= 3* 2/3x - 18

y=2/3x
-x=-12

x=12
y=8

8 4 8
Najlepsza Odpowiedź!
2009-12-01T15:58:07+01:00
X- pierwsza liczba
y- druga liczba

x/y = 3/2
2x = 3y

x-6 = 3(y-6)
x-6 = 3y-18
x-6 = 2x-18
-x = -12
x = 12

2x = 2y
2×12 = 2y
24 = 3y
y = 8

x=12
y=8
33 4 33